2019
DOI: 10.3390/polym11020378
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Laser Fabrication of Engineered Functional Surfaces Based on Biodegradable Polymer and Biopolymer/Ceramic Composite Thin Films

Abstract: Surface functionalization introduced by precisely-defined surface structures depended on the surface texture and quality. Laser treatment is an advanced, non-contact technique for improving the biomaterials surface characteristics. In this study, femtosecond laser modification was applied to fabricate diverse structures on biodegradable polymer thin films and their ceramic blends. The influences of key laser processing parameters like laser energy and a number of applied laser pulses (N) over laser-treated sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 57 publications
(98 reference statements)
0
8
0
Order By: Relevance
“…Similar results were described for other polymer types. Femtosecond laser treatment favorably influenced attachment and orientation of mouse calvaria osteoblasts and human adipose derived mesenchymal stem cells on thin films of pure chitosan and composite blends of chitosan (Ch)/HAp/ZrO 2 [ 62 ]. The authors of another work [ 83 ] studied human osteoblasts ATCC cultured on the surface of poly(L-lactide)/hydroxyapatite films modified using femtosecond laser and did not detect any cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar results were described for other polymer types. Femtosecond laser treatment favorably influenced attachment and orientation of mouse calvaria osteoblasts and human adipose derived mesenchymal stem cells on thin films of pure chitosan and composite blends of chitosan (Ch)/HAp/ZrO 2 [ 62 ]. The authors of another work [ 83 ] studied human osteoblasts ATCC cultured on the surface of poly(L-lactide)/hydroxyapatite films modified using femtosecond laser and did not detect any cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…and adapt structural and physical properties of film surface to cell engineering applications. Daskalova et al [ 62 ] reported using femtosecond laser modification to produce various structures of thin films of biodegradable polymers and their ceramic blends (pure chitosan thin films and different percentage of composite blends of chitosan (Ch)/HAp/ZrO 2 thin films). Laser treatment increased film surface roughness and enhanced attachment and orientation of eukaryotic cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ortiz et al reported that the laser ablation of poly-L-lactic acid (PLLA) is governed by a multi-photon process in the three cases of interaction: with the fundamental (1064 nm), the second (532 nm) and the third harmonic generation wave (355 nm) of Nd: YVO 4 laser [ 65 ]. The group of Daskalova et al, for example, achieved 3D porous structures composed of µm-sized porous foam on the surface of collagen, elastin and chitosan thin films by femtosecond laser structuring at ƛ = 800 nm in which cells adhere, elongate, and orientate [ 66 , 67 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…Considering the laser regime in the literature, femtosecond beams are less employed for polymer-thin-films processing [ 41 , 42 ], and particularly with UV beams, as investigated in the present work. The advantage of the femtosecond (fs) regime compared to the nanosecond one is that the LIPSS could be formed despite the low absorption coefficient of the polymers [ 43 ].…”
Section: Introductionmentioning
confidence: 99%